“ANÁLISIS JURÍDICO Y DOCTRINARIO DE LA SENTENCIA SOBRE SANCIONES EN CONTEXTOS EDUCATIVOS, SENTENCIA NO. 456-20JP/21” - SÁNCHEZ RIVERA, SANTIAGO MATEO (2024)
This research work is based on the legal and doctrinal analysis of the sentence number 456- 20 JP/ 21 that exposes the administrative sanctions in educational contexts, in this case sanctions applied to a student who incurred in the violation of rights such as due process, the correct application of restorative justice and the right to education, it is necessary to emphasize that educational centers are learning communities whose purpose is to satisfy the right to education as stipulated in the constitution, in addition to these educational centers have coexistence codes that are public documents constructed by the actors of the educational communities that maintain principles, objectives and institutional policies that regulate the relations between the members of the educational communities. Educational centers maintain their autonomy, rules and procedures for resolving conflicts and sanctions, which must be based on the rights of children and adolescents as a group of priority attention and protected by the principle of the best interest of the child, as well as the principle of restorative justice through an inclusive and dialogic participatory learning established within the educational coexistence codes. Conflict resolution within educational centers motivates to maintain a culture of peace, in addition to identifying and preventing conflicts among the members of the educational communities. Through this study and the legal and doctrinal analysis, the violation of rights has been identified within the administrative sanctioning processes in educational centers, so it is necessary to propose strategies and mechanisms for conflict resolution based on rights and restorative justice on issues such as Sexting, which was a practical activity within an educational center and sanctioned under the taboo and the violation of rights.